Political Reforms in Jordan: Between the Wagers of Monarchy and the Pressures of Opposition and Popular Movements - Al Sarhan, Atallah; AlShdouhi, Emad (Dirasat: Human and Social Sciences, 2019)
This study aims at shedding light on the political reforms in Jordan, particularly in the period following the Arab Spring revolutions, through studying and analyzing the royal vision of political reform (represented by the High Commissioning Decrees, Royal Initiatives and Discussion Papers), the vision of the executive authority for political reform, and the partisan and popular vision of political reform. The study found that the political reforms in Jordan are still below the required level, and that the balance of power between the political regime and the forces of popular movement and opposition currents has not reached a stage that leads the political regime to accept substantive concessions. The success of the political regime in implementing its vision of reform has helped to break down the forces of popular mobility into regional movements and local movements, each shaping its own vision of reform according to its own agenda, with no coordination and complementarity among these movements.